2011
DOI: 10.1371/journal.pone.0021944
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Tropism, Population Dynamics, Host Range and Taxonomic Status of an Aphid Secondary Symbiont, SMLS (Sitobion miscanthi L Type Symbiont)

Abstract: SMLS (Sitobion miscanthi L type symbiont) is a newly reported aphid secondary symbiont. Phylogenetic evidence from molecular markers indicates that SMLS belongs to the Rickettsiaceae and has a sibling relationship with Orientia tsutsugamushi. A comparative analysis of coxA nucleotide sequences further supports recognition of SMLS as a new genus in the Rickettsiaceae. In situ hybridization reveals that SMLS is housed in both sheath cells and secondary bacteriocytes and it is also detected in aphid hemolymph. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Recently, Singh et al (30) reported that of the 14 whitefly populations belonging to the Asia I and Asia II genetic groups of B. tabaci from different locations in north India, OLO was present in 7. Apart from whiteflies, bacteria belonging to the same genus as OLO have so far been reported only in genera of the family Aphididae (19,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Singh et al (30) reported that of the 14 whitefly populations belonging to the Asia I and Asia II genetic groups of B. tabaci from different locations in north India, OLO was present in 7. Apart from whiteflies, bacteria belonging to the same genus as OLO have so far been reported only in genera of the family Aphididae (19,31).…”
Section: Discussionmentioning
confidence: 99%
“…Hemipteriphilus asiaticus" and the aphid symbiont SMLS (98.8% on average) places them within the genus "Candidatus Hemipteriphilus." So far, "Candidatus Hemipteriphilus" has been detected only from Asian populations of Hemiptera (15,19,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchnera density was higher in newly adult A. glycines feeding on healthy soybean than in younger aphids. Although Buchnera titre varied across host development among Acyrthosiphon pisum clones (Vogel & Moran, ), a similar pattern was reported in Sitobion miscanthi (Li et al ., ). Increased Buchnera titre was also found between 5‐ and 7‐day‐old S. graminum , although distinct stages of development were not defined (Baumann & Baumann, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no SMLS infections have been detected in the wheat seedlings after SMLS‐infected aphids fed on them (Li et al . ). SMLS and its closest relative OLO (Orientia‐like organism) are grouped into a new genus of family Rickettsiaceae, Candidatus Hemipteriphilus (Bing et al .…”
Section: Introductionmentioning
confidence: 97%